Pertanggungjawaban Pidana Korporasi terhadap Dugaan Tindak Pidana Suap dalam Izin Ekspor CPO (Crude Palm Oil) PT Wilmar Group - Ghaitsa Zahira Sofiyah; Arman Tjoneng (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The growth of large corporations in Indonesia poses risks of legal violations such as corruption and bribery. This study examines the consistency of legal application against PT. Wilmar Group in the alleged bribery case of CPO export permits, as well as corporate criminal liability under the Corruption Law. A normative juridical approach is used to analyze the application of the acquittal verdict and the recovery of state losses. The findings indicate inconsistent legal application, with the focus on individual prosecutions being more prevalent than corporate ones, despite the apparent state losses. The study highlights the obstacles in proving corporate wrongdoing and the importance of fair and consistent law enforcement against corporations subject to criminal law.